2001
DOI: 10.1007/s11882-001-0036-0
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant allergens/ allergen standardization

Abstract: Recombinant allergens are genetically engineered isoforms representing allergen molecules from allergen extracts. Immunologic responses of allergic patients toward allergen extracts define the major allergens. For the average allergic patient, the diagnostic sensitivity and treatment efficacy correlate with the concentration of major allergen. Standardization of allergen products (extracts or genetically engineered allergens) can therefore advantageously be performed using a selected recombinant major allergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Although it is possible to determine the quantity of certain allergens in therapeutic allergen extract, but it is not achievable to eliminate non-allergenic components [26]. It has been reported that extractbased immunotherapy may induce IgE antibodies toward the new allergens and lead to clinically relevant new sensitizations [6].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is possible to determine the quantity of certain allergens in therapeutic allergen extract, but it is not achievable to eliminate non-allergenic components [26]. It has been reported that extractbased immunotherapy may induce IgE antibodies toward the new allergens and lead to clinically relevant new sensitizations [6].…”
Section: Discussionmentioning
confidence: 99%
“…Sublingual vaccines prepared from raw allergic materials, such as grass or tree pollens, 16,17 are previously exposed to both macroscopic and microscopic examination in order to determine electrophoretic profiling and evaluate of bacteriological load and biological activity.…”
Section: Allergen Standardization(s)mentioning
confidence: 99%
“…Sublingual vaccines based on aqueous allergen extracts are currently prepared from raw allergenic materials, such as grass or tree pollens, cat or dog epithelia, or cultures of common house dust mites (1–6). Quality control of raw materials includes both macroscopic and microscopic examination to determine protein content, electrophoretic (isoelectrofocusing) profiling, and evaluations of bacteriological load and biological activity.…”
Section: The Quality Of Sublingual Vaccinesmentioning
confidence: 99%